Analisis Swot Dalam Menentukan Strategi Pemasaran Produk Kopi Sanggabuana: Studi Kasus Pada Usaha Bumdes Buanamekar Di Desa Mekarbuana Karawang - Neni Sumarni; Syifa Pramudita Faddila (Bulletin of Management and Business, 2023)
Sanggabuana coffee is a coffee product produced from Mekarbuana Karawang Village. Processing into coffee packaging if Bumdes Buanamekar. Marketing for KoSa products is still experiencing difficulties and obstacles, promotions that have not been widespread and conventional marketing is still a major problem in sales so that the sales volume is not optimal. This study aims to determine the strengths and weaknesses of Bumdes Buana Mekar coffee business, the position of Bumdes business and the right marketing strategy for Bumdes Buana Mekar. The method used in this study is descriptive qualitative, with the method of observation, interviews, documentation studies and analyzed using SWOT analysis. Data analysis using IFAs and EFAS by analyzing internal and external factors, Strengths, Weaknesses, Opportunities, and Threats to obtain strategic positions. This research is expected to make a positive contribution to Bumdes Buana Mekar in implementing its marketing strategy so as to increase sales of Sanggabuana coffee products (KoSa).